The Therapeutic Dimensions of the Soul in Al-Ghazali: A Study of Islamic Psychotherapy - Sadrul Eslam Tarihi; Akhmad Rofii Damyati (VIRTUOUS JOURNAL, 2025)
This article examines the therapeutic dimensions of the soul (nafs) in the thought of Al-Ghazali and explores its relevance for contemporary Islamic psychotherapy. Grounded primarily in al-Ghazali’s magnum opus Iḥyāʾ ʿUlūm al-Dīn, the study employs a qualitative textual and conceptual analysis to reconstruct his model of the human psyche and its mechanisms of healing. Al-Ghazali conceptualizes the human being as an integrated entity composed of the nafs, qalb, ʿaql, and rūḥ, where psychological disturbances arise from imbalances among these interrelated faculties. Unlike modern reductionist approaches that isolate mental disorders from spiritual conditions, al-Ghazali frames psychological illness as a manifestation of moral and spiritual disorientation, including diseases of the heart such as envy, arrogance, and excessive attachment to worldly desires. The study further demonstrates that al-Ghazali proposes a structured therapeutic process centered on tazkiyat al-nafs (purification of the soul), mujāhadah (self-discipline), and riyāḍah (spiritual training), supported by cognitive reorientation through maʿrifah (knowledge of God and the self). These elements collectively form a holistic psychotherapeutic system that integrates ethical refinement, cognitive transformation, and behavioral regulation. The findings suggest that al-Ghazali’s model anticipates key aspects of contemporary therapeutic approaches, such as cognitive restructuring and mindfulness, while maintaining a distinct theocentric orientation. This research contributes to the development of an Islamically integrated psychotherapy framework by offering a systematic reconstruction of al-Ghazali’s therapeutic psychology and highlighting its enduring relevance in addressing modern psychological challenges.